Editorial: No smoke without fire: Recreational cannabis use among South Sudanese youth - Nyakomi Adwok (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2024)
'Bangi', 'ganja', 'weed', 'grass', and 'herb' are a handful of names for psychoactive preparations of the Cannabis sativa plant. According to the World Health Organisation (WHO), cannabis is the world's "most widely cultivated, trafficked and abused illicit drug."[1] Compared to substances like cocaine or heroin, recreational cannabis use enjoys a somewhat sanitised reputation as a 'natural' panacea for issues ranging from insomnia to social anxiety. This perception is further complicated by the legitimate applications of medicinal cannabis and cannabinoids, which under professional supervision, have shown efficacy in alleviating symptoms of conditions such as epilepsy and multiple sclerosis.[2] In a qualitative study of drug and alcohol use among South Sudanese youth in Australia, Pittaway and Dantas found that most participants did not consider cannabis as a drug.[3] Additionally, many participants reported that cannabis was beneficial for mental health issues and linked it to positive states like relaxation, creativity and freedom.